Rapid escalation and release of risks to forest ecosystems triggered by warming: Insights from tree growth synchrony in temperate forests - Liangjun Zhu; Danyang Yuan; J. Julio Camarero; David J. Cooper; Mai-He Li; Shuguang Liu; Xiaochun Wang; Paolo Cherubini (Forest Ecosystems)
Tree growth synchrony serves as a valuable ecological indicator of forest resilience to climate stress and disturbances. However, our understanding of how increasing temperature affects tree growth synchrony during rapidly and slowly warming periods in ecosystems with varying climatic conditions remains limited. By using tree-ring data from temperate broadleaf (Fraxinus mandshurica, Phellodendron amurense, Quercus mongolica, and Juglans mandshurica) and Korean pine (Pinus koraiensis) mixed forests in northeast China, we investigated the effects of climate change, particularly warming, on the growth synchrony of five dominant temperate tree species across contrasting warm-dry and cool-wet climate conditions. Results show that temperature over water availability was the primary factor driving the growth and growth synchrony of the five species. Growth synchrony was significantly higher in warm-dry than in cool-wet areas, primarily due to more uniform climate conditions and higher climate sensitivity in the former. Rapid warming from the 1960s to the 1990s significantly enhanced tree growth synchrony in both areas, followed by a marked reversal as temperatures exceeded a certain threshold or warming slowed down, particularly in the warm-dry area. The growth synchrony variation patterns of the five species were highly consistent over time, although broadleaves exhibited higher synchrony than conifers, suggesting potential risks to forest resilience and stability under future climate change scenarios. Growing season temperatures and non-growing season temperatures and precipitation had a stronger positive effect on tree growth in the cool-wet area compared to the warm-dry area. High relative humidity hindered growth in the cool-wet area but enhanced it in the warm-dry area. Overall, our study highlights that the diversity and sensitivity of climate-growth relationships directly determine spatiotemporal growth synchrony. Temperature, along with water availability, shape long-term forest dynamics by affecting tree growth and synchrony. These results provide crucial insights for forest management practice to enhance structural diversity and resilience capacity against climate change-induced synchrony shifts.